Manajemen Strategi Wakil Kepala Sekolah Bidang Kesiswaan dalam Meningkatkan Mutu Organisasi Siswa Intra Madrasah Di Ma Palapa Nusantara NW Selebung - M. Saipul Watoni; Ozi Satria; Sri Novi Handayani (Pendidikan Al-Gafari, 2024)
Management studentship is a series of activities that have been planned and developed for students so they can carry out activities Study teach effectively and efficiently starting from reception student until graduation student from school. Study aim for know how field waka planning studentship in enhancement quality of OSIM, implementation of student programs in enhancement OSIM quality and field deputy strategy evaluation studentship in enhancement OSIM quality at MA Palapa Nusantara NW Selebung. Types of research This is qualitative. technique data collection used use method interviews, observation, and documentation. data analysis using data reduction, data presentation, and withdrawal conclusion. whereas checking wetness study uses triangulation, persistence observation, and approach based on forever study. Results of the study show that management deputy head of field Strategy studentship in enhancement OSIM quality at MA Palapa Nusantara NW Selebung namely: 1) Field waka planning studentship in increase the quality of the OSIS at MA Palapa Nusantara NW Selebung with carry out meeting, handover design to Head schools and outreach programs to OSIM member. 2) Implementation of the field waka strategy studentship in enhancement OSIS quality is appropriate with planning beginning. In implementing the OSIM program, the OSIM Advisor and Deputy Head of Student Affairs always guide and supervise the course of the program. 3) Evaluation of Deputy Head of Field Strategy studentship in enhancement OSIM quality at MA Palapa Nusantara NW Selebung held after program implementation. Evaluation of the aim for evaluating program implementation and overcoming problems during implementation of programs for more implementation Good again.